Energy saving in industrial plants study aid - Klimova specialist in the field of power engineering Associate Professor of Tomsk Polytechnic University, Candidate of technical sciences; Shanenkov specialist in the field of electric power engineering Associate Professor of the Department of Tomsk Polytechnic University, Candidate of Sciences; Rakhmatullin specialist in the field of electric power engineering Associate Professor of Tomsk Polytechnic University, Candidate of Sciences; Surkov Specialist in the field of electric power engineering Associate Professor of Tomsk Polytechnic University, Candidate of technical sciences (TPU Publishing House, 2021)
The textbook deals with the issues studied in the course "Energy saving and energy audit of industrial plants". There are given: the structure of the regulatory base for energy saving; the practice of contractual relationships between consumers and energy supplying organizations; the requirements for the organization and mandatory energy audits, for the preparation and approval of an energy passport and energy saving program; the assessment of payments by different price categories; the energy-saving solutions, which are standard and generally available for implementation in power supply systems of consumers. It is intended for students studying in the direction 13.04.02 "Power engineering and electrical engineering".